ISOLATION FROM ALEXA-LEIOPETALA AND X-RAY CRYSTAL-STRUCTURE OF ALEXINE, (1R,2R,3R,7S,8S)-3-HYDROXYMETHYL-1,2,7-TRIHYDROXYPYRROLIZIDINE [(2R,3R,4R,5S,6S)-2-HYDROXYMETHYL-1-AZABICYCLO[3.3.0]OCTAN-3,4,6-TRIOL], A UNIQUE PYRROLIZIDINE ALKALOID - Nash, R; Fellows, L; Dring, J; Fleet, G; Derome, A; Hamor, T; Scofield, A; Watkin, D (1988)
The isolation from Alexa leiopetala and identification by X-ray crystal structure analysis of (1R,2R,3R,7S,8S)-3-hydroxymethyl-1,2,7-trihydroxypyrrolizidine [(2R,3R,4R,5S,6S)-2-hydroxymethyl-1-azabicyclo[3.3.0]octan-3,4,6-triol], a unique pyrrolizidine alkaloid, is described. A preliminary study of the inhibition of glycosidases by alexine is reported. © 1988.